Constantin Brancusi vu par Benjamin Fondane - Hélène Lenz (Recherches, 2016)
Based on a testimony of the musician Marcel Mihalovici, the article first calls to mind Brancusi in Paris when Fundoianu / Fondane settles down there. In the French capital, the sculptor maintains the style of life of a “Danubian peasant”. He mistrusts the writers but realizes a drawing (portrait) of the young poet and philosopher. In turn, Fondane devotes to him the portrait “Constantin Brancusi” which is one of his best reviews, as the essay on Chagall and “Le faux traité d’esthétique”. He shows that the inspiration of the sculptor—as seen by Fondane—is not reducible to the materiality of the plastic art. Purified, it is a part of modern poetry, it creates a lexicon founding a new language, artisan skills, mathematics and religious expression.